If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(11 + -1m) = 5(m + -7) (11 * -9 + -1m * -9) = 5(m + -7) (-99 + 9m) = 5(m + -7) Reorder the terms: -99 + 9m = 5(-7 + m) -99 + 9m = (-7 * 5 + m * 5) -99 + 9m = (-35 + 5m) Solving -99 + 9m = -35 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -99 + 9m + -5m = -35 + 5m + -5m Combine like terms: 9m + -5m = 4m -99 + 4m = -35 + 5m + -5m Combine like terms: 5m + -5m = 0 -99 + 4m = -35 + 0 -99 + 4m = -35 Add '99' to each side of the equation. -99 + 99 + 4m = -35 + 99 Combine like terms: -99 + 99 = 0 0 + 4m = -35 + 99 4m = -35 + 99 Combine like terms: -35 + 99 = 64 4m = 64 Divide each side by '4'. m = 16 Simplifying m = 16
| -6*5= | | 68=18+1/220L | | 6r-5r=-2(7-7r)-12(9-4r) | | p=2(8)+2(10) | | 4(u+5)(-u-1)=0 | | log(x)=0.73 | | 1.4m-0.8(XML-2)=2.4m | | 1/10=4/5x | | 4x^2+12x=-2 | | X/2+3=17 | | 18b=2(12b+7) | | 5/2=4x/3 | | 6/7+2/7 | | 5x+5-4x=10 | | 35=-2x-14 | | -1/2y+3(y+2)=12 | | -5*1-4y=20 | | -14x^2w*y^7w/4x^6w*y^3v | | (v+5)(v-7)=0 | | 1/2x-3/4x+5/83/2x-5/2 | | -3(2x-4)=-6 | | 0.4-7=1.4x | | -9(4x-8)-6(-2x-7)=78 | | -4-3(5n-6)=-26-5n | | 0.4-7=1.4 | | -4-4(2-7n)=-4(6-7n)-7 | | 1/2x-3/4x+5/8-3/2x-5/2 | | d=60(8) | | (x^2-x-2)/(x^2-4) | | y=-3*1-6 | | 6x-3+5=7 | | 3/4t-7/12t=1 |